Effects of Corporate Governance and Capital Structure on Firms’ Performance: Evidence from Major Sectors of Pakistan - Ahmed, Farhan; Talreja, Suman; Kashif, Muhammad (The Indonesian Capital Market Review, 2018)
This study aims to examine the effects of corporate governance and capital structure on firm’s performance. Panel pooled regression method were applied on annual data of two major sectors: automobile & fertilizers from 2006 to 2016. Findings show that board size have positive relationship & audit committee has negative relationship with profitability of automobile sector and vice versa for fertilizers sector. Capital structure is measured by current ratio, debt to equity, short term & long term debt whereas profitability is measured by ROA and ROE. Positive relation of current ratio and profitability of both sectors is observed and the negative relationship of debt to equity of both the sectors has been observed whereas short and long-term debt has no significant relationship in fertil- izers sector. The results should be of great importance to investors, creditors, financial analysts and academicians especially after global financial crisis and collapses of giant organizations worldwide.